Allergic bronchopulmonary aspergillosis a report of four cases with literature review - Xu, Hui (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2015)
OBJECTIVE: To understand the clinical characteristics of allergic bronchopulmonary aspergillosis (ABPA) so as to diagnose and treat the disease earlier